Protein-Rich Extract from the Bagrid Catfish Pelteobagrus fulvidraco Improves Exercise Performance and Anti-Fatigue - Lee, Gong-Hyeon; Harwanto, Dicky; Choi, Jae-Suk; Kim, Mi-Ryung; Jin, Deuk H.; Jin, Hyung-Joo; Hong, Yong-Ki (Current Nutrition & Food Science, 2017)
Background: The freshwater bagrid catfish, Pelteobagrus fulvidraco, is used in hot chowder or tonic soup, and it has become a favorite inland aquaculturable species in Asian countries. To investigate the claims regarding its beneficial effects, we examined physical exercise performance in mice fed protein-rich P. fulvidraco extract. Methods: Mice were fed P. fulvidraco extract (25 mg/mL) orally once per day for 1 week at a dose of 10 μL/g body weight, and then forelimb grip strength, swimming endurance, body weight, and blood biochemical indicators were examined. Results: Bagrid catfish extract significantly enhanced grip strength to 1.25 ± 0.04 N (P < 0.01), which was 23% higher than that on day 0. The extract also increased swimming endurance to 86 ± 10 sec (P <0.05), which was 46% higher than that on day 0. After the gripping exercises, the blood glucose level was significantly increased to an average of 222% compared with the control level. Lactate dehydrogenase and glutathione peroxidase levels were also significantly increased by 350% and 205%, respectively. The urea level in blood serum was 60% compared with control. In addition, triglyceride and cholesterol levels decreased to 69% and 73%, respectively, in extract-fed mice. Conclusion: Bagrid catfish extract improved exercise performance and fatigue recovery by providing more blood glucose and decreasing lactate and oxidative stress caused by exhaustive exercise.
Keywords: exercise performance